The predictive value of on-ice special tests in relation to various indexes of aerobic and anaerobic capacity in ice hockey players - Roczniok, R.; Maszczyk, A.; Czuba, M.; Stanula, A.; Pietraszewski, P.; Gabrys, T. (Human Movement, 2012)
The main goal of this study was to determine the predictive value of the indexes of aerobic and anaerobic endurance in relation to specific on-ice tests performed by hockey players that focus on strength, power, speed as well as speed and strength endurance. Methods. Ice hockey players, who were members of the U20 (under 20 years of age) Polish National Ice Hockey Team, were selected from the Athletic School in Sosnowiec, Poland. Parameters that determine anaerobic and aerobic capacity were evaluated and a special physical fitness assessment was made based on a battery of ice-hockey specific tests. The degree and direction of correlations between the individual parameters of anaerobic and aerobic endurance and the special physical fitness test were calculated. Results. The obtained results found significant correlations between maximal power obtained from the Wingate test and certain aspects of the special physical fitness test, specifically the 6 × 9 turns, 6 × 9 stops and 6 × 30 m endurance tests. Significant correlations of the above-mentioned special physical fitness tests were also observed with the aerobic capacity parameter, VO2max. Conclusions. The obtained results could be considerably useful in training, as well as providing much more information on athletes which can then be suited for more personalized forms of training